The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/en13215536
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Harmonic Influence on Electrical Energy Metering

Abstract: The paper considers the influence of harmonics on the operating of electrical energy meters in a network with nonlinear loads. It is shown that electronic static meters of active energy are tested in the presence of distortions, and electronic static meters of reactive energy accuracy requirements do not take into account the possible presence of harmonics. It is revealed that the maximum influence on the error in active energy metering is exerted by the number of harmonics taken into account and their amplitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…In turn, the optimization of modes of operation of equipment, especially for thermal power generation and the reduction of necessary maneuverability will allow for the reduction of specific operating costs (including fuel costs) and CO 2 emissions. In addition, this will extend the service life of existing equipment, while reducing the need to build new facilities [29]. In the case of network equipment, network losses will naturally be decreased by reducing the volume of overflows.…”
Section: Diffusion Of Ress Into Existing Energy System Through the Development Of Power Accumulatorsmentioning
confidence: 99%
“…In turn, the optimization of modes of operation of equipment, especially for thermal power generation and the reduction of necessary maneuverability will allow for the reduction of specific operating costs (including fuel costs) and CO 2 emissions. In addition, this will extend the service life of existing equipment, while reducing the need to build new facilities [29]. In the case of network equipment, network losses will naturally be decreased by reducing the volume of overflows.…”
Section: Diffusion Of Ress Into Existing Energy System Through the Development Of Power Accumulatorsmentioning
confidence: 99%
“…In practice, such conditions are hard to achieve. It is worth noting that, in [24], the authors noticed the influence of harmonics on the operating of electrical energy meters in a network with nonlinear loads. It is shown that electronic static meters of active energy are tested in the presence of distortions, and electronic static meters of reactive energy accuracy requirements do not take into account the possible presence of harmonics.…”
Section: Gap In the Research Related To Influence Of Supply Voltage D...mentioning
confidence: 99%
“… Source of non-intentional emissions and propagation of supraharmonics, interaction between devices [16][17][18][19][20].  Potential problems with communication via the power grid [1,[20][21][22][23][24][25].…”
mentioning
confidence: 99%
“…To provide proper reaction for power quality disturbances, the control systems of relay protection units and compensation devices must be capable of fast and accurate tracking of both voltages and currents parameters in the industrial power grids [36][37][38][39]. To achieve this, well-known algorithms based on space vector and instantaneous power estimation are used [36,40,41].…”
mentioning
confidence: 99%
“…Considering the remoteness of the dragline #2 and #3 from the transformer bus, the presented load profile will create a significant voltage drop in the cable lines, connecting the grid node with the substation bus, depending on the grid short-circuit impedance at the substation bus [57]. At the same time, dragline #3 will consume harmonic currents with arbitrary magnitude, depending on its load profile, therefore, introducing randomness to currents and voltages spectra at the PCC [38,58,59]. To maintain power quality within the acceptable limits, which are regulated according to GOST (acronym for State Standard or Governmental Standard in Russian) 32144-2013, the dynamic compensators are typical to be installed at the nodes depending on the grid and load configuration.…”
mentioning
confidence: 99%